The Dynamics of Postnominal Adjectives in Middle English - Veronika Volná; Pavlína Šaldová (Anglica. An International Journal of English Studies)
Middle English was a period of transition between the free word order of Old English, with functional variation of adjective form and position with respect to the head noun, and the fixed prenominal placement of single attributive adjectives in Modern English. Aided by the PPCME2 of the Penn-Helsinki corpora, this corpus-driven study explores the range of adjectives attested frequently after the head noun, as well as their relative attraction to the position and, sampling the ME period with emphasis on variables in the corpus metadata, compares the frequencies of postnominally placed adjectives in various genres, capturing their declining overall frequency over time. These general tendencies are commented against the background of postpositives in PDE.